Synthesis of L-cysteine-CdSe Quantum Dots for optical Biosensing Application - Ajeel, Thalfaa Rasheed; Abdullah, Manal Midhat; Lafta, Fadhel Mohammed (Iraqi Journal of Physics, 2025)
Cadmium selenide (CdSe) nanocrystals, modified with water-soluble L-cysteine and known as CdSe/Cys nanocrystals, were synthesized using L-cysteine as a stabilizing agent. This synthesis process ensured the formation of highly stable nanocrystals with desirable properties for various applications. The CdSe/Cys nanocrystals were carefully studied using advanced methods to understand their structure, composition, and optical features in detail. The peak that shows the preferred (111) orientation of L-cysteine-capped CdSe matches the usual core components, as indicated by the XRD pattern. On the other hand, the peaks at (220) and (311) are not as prominent. Photoluminescence (PL) spectroscopy was conducted to study the optical properties of the CdSe/Cys nanocrystals. The PL spectra’s strong fluorescence emission showed these nanocrystals’ excellent quantum efficiency. The emission peak was sharp and well-defined, highlighting the uniformity in size and composition of the synthesised nanocrystals. The study revealed the robust fluorescence of the spherical CdSe/Cys nanoparticles, with an average diameter of 2.3 nm. Modifying the surface of CdSe nanoparticles with cysteine improved their water solubility and biocompatibility.